1992
DOI: 10.1016/0022-510x(92)90245-g
|View full text |Cite
|
Sign up to set email alerts
|

Expression of CD45RC and Ia antigen in the spinal cord in acute experimental allergic encephalomyelitis: An immunocytochemical and flow cytometric study

Abstract: We performed immunocytochemical studies to analyze the inflammatory infiltrate and major histocompatibility complex class II (Ia) antigen expression in the spinal cord of Lewis rats with acute experimental allergic encephalomyelitis (EAE) induced by inoculation with myelin basic protein and adjuvants. Using antibodies to lymphocyte markers and other monoclonal antibodies we found that during clinical episodes the inflammatory infiltrate was chiefly composed of T lymphocytes and macrophages. The majority of cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

1994
1994
2005
2005

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 38 publications
1
14
0
Order By: Relevance
“…In the later episodes of CR-EAE, prominent Ia expression on cells of dendritic morphology was observed with immunocytochemistry, and increased numbers of Ia + cells, including FSC low cells typical of microglia, were found with flow cytometry. In the CNS, Ia can be expressed on infiltrating lymphocytes, macrophages and microglia and has been widely described in acute EAE (Matsumoto et al, 1986;Vass et al, 1986;Konno et al, 1989;McCombe et al, 1992). In this model of CR-EAE, widespread Ia expression in the CNS was found 50 days after inoculation (Polman et al, 1988).…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…In the later episodes of CR-EAE, prominent Ia expression on cells of dendritic morphology was observed with immunocytochemistry, and increased numbers of Ia + cells, including FSC low cells typical of microglia, were found with flow cytometry. In the CNS, Ia can be expressed on infiltrating lymphocytes, macrophages and microglia and has been widely described in acute EAE (Matsumoto et al, 1986;Vass et al, 1986;Konno et al, 1989;McCombe et al, 1992). In this model of CR-EAE, widespread Ia expression in the CNS was found 50 days after inoculation (Polman et al, 1988).…”
Section: Discussionmentioning
confidence: 64%
“…In rats with acute EAE induced by inoculation with whole CNS tissue or MBP, the majority of the T cells in the spinal cord are CD4 + CD45RC McCombe et al, 1992). In mice with acute EAE induced by the passive transfer of labelled, MBP-sensitized lymph node cells, the labelled cells in the CNS are CD45RB low (equivalent to our CD45RC − ) (Zeine and Owens, 1992).…”
Section: Discussionmentioning
confidence: 98%
“…The development of EAE in Lewis rats is associated with infiltration of the nervous system by T-lymphocytes and macrophages (Hickey et al, 1983;McCombe et al, 1992), followed by demyelination of the central nervous system and the nerve roots. We have recently shown that recovery from passively transferred and actively induced MBP-EAE is associated with a selective elimination of V 8.2 + MBP-reactive T-cells from the spinal cord by apoptosis (Tabi et al, 1994 andTabi et al, 1995;McCombe et al, 1996) and have suggested that this apoptosis may represent activation-induced cell death of T-lymphocytes in the target organ of this autoimmune disease Tabi et al, 1994 andTabi et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…EAE is the best available animal model of multiple sclerosis. Recovery from EAE is associated with loss of T-lymphocytes from the central nervous system (CNS) (Matsumoto and Fujiwara, 1987;McCombe et al, 1992;Zeine and Owens, 1993) and apoptosis of these lymphocytes in the CNS (Pender et al, 1991 andPender et al, 1992;Schmied et al, 1993). In the Lewis rat, the encephalitogenic lymphocytes in EAE induced by inoculation with myelin basic protein (MBP) (MBP-EAE) are predominantly V 8.2 + (Offner et al, 1993;Tsuchida et al, 1993;Imrich et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…It can be induced by inoculation with myelin proteins, such as myelin basic protein (MBP), and adjuvants and can be passively transferred to naive animals by CD4 + T cells (Pettinelli and McFarlin, 1981). EAE is characterized by infiltration of the nervous system with activated T lymphocytes and macrophages (Raine, 1984;McCombe et al, 1992). Cloned encephalitogenic T cells secrete interleukin-2 (IL-2) and interferon-(IFN-) (Ando et al, 1989;Baron et al, 1993).…”
Section: Introductionmentioning
confidence: 99%